TRADITIONAL CULTURE AND NATIONAL IDENTITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In defining and studying national identity, one of the necessary conditions is to understand the connection of its essence and content with the national traditional culture. The traditional culture of a nation in the context of historical conditions and social destiny has a direct impact on the formation and realization of national identity, on the manifestations and demonstrations of such identity in the outside world. In this paper some aspects of the relationship between traditional culture and national identity are considered in a philosophical and methodological way. It is emphasized that the scientific-theoretical analysis of the nature and content of such a relationship first of all requires comprehension of its temporal dimensions. Philosophy (ontology) asserts the inseparable connection between the problem of being and the question of time, and believes that time is the horizon of understanding of being. An important condition for comprehending national being in the historical context is to consider it in unity with such dimensions of time as past, present and future. Of course, depending on historical conditions, traditional culture itself is constantly transformed and renewed. Preservation of its own essence and the main features of this culture as the core of the historical process determines the identity of the bearers of this culture, is constantly strengthened and enriched. In the self-determination of the nation, in its relationship with the surrounding world, the being basis of its historical development is constantly reproduced, transmitted from generation to generation through the mechanisms of tradition, is present in the way the nation responds to the challenges of time, how it defines its historical place in the world. Therefore, along with economic, technological, environmental, political, social and other factors, it is important to realize the ontological basis of the inseparable relationship between traditional culture and national identity. In this paper, the empirical basis for the discussion of theoretical issues is Kyrgyz national culture.
Keywords: traditional culture, national identity, national being, time, Kyrgyz culture, musical tradition, historical conditions, thinking about the future.